Dielectric and piezoelectric properties of PZT type ceramics obtained by the sol-gel method - Dukat, Monika; Zarycka, Aldona (Archives of Acoustics, 2007)
A sol-gel method belongs to chemical methods of producing non-organic and nonmetallicmaterials. As a result of a synthesis by the sol-gel method a powder with thePb(Zr$_{0.35}$Ti$_{0.65}$)O$_{3}$ chemical composition, which was formed and sintered freely, and hotpressed as well, was obtained. The obtained ceramic material was subjected to test of propertiesof permittivity, loss tangent and piezoelectric properties as well. Both a description of atechnological process to obtain ceramic materials by the sol-gel method and the determineddielectric and piezoelectric parameters of the ceramic in question are presented in this work.The ceramic in question can be used, among others, in pressure sensors, electroacoustic transducers,piezoceramic amplifiers, loudspeakers and microphones.